THE EFFECT OF SWIMMING EXTRACURRICULAR PROGRAMS ON THE PHYSICAL FITNESS AND MENTAL HEALTH OF MIDDLE SCHOOL STUDENTS - M. Imran Hasanuddin; Silatul Rahmi; Asri Awal (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Physical fitness and mental health are important aspects in the development of high school students. Physical activity, including sport, plays a role in improving students' physical and psychological well-being. Swimming as a form of exercise that involves the whole body has been proven to provide various health benefits. This study aims to analyze the effect of extracurricular swimming programs on the physical fitness and mental health of secondary school students through a systematic literature review. The study results showed that the swimming program significantly improved students' physical fitness by increasing cardiovascular endurance, muscle strength, flexibility, and body coordination, as well as reducing the risk of injury compared to land-based sports. From a mental health aspect, swimming contributes to reducing stress, anxiety and depression through the release of endorphins and the relaxing effects produced by water activities. Apart from that, swimming also helps increase self-confidence, build social interactions, and supports a healthy lifestyle in the long term. The implications of this research emphasize the importance of support from schools and related parties in implementing an effective swimming extracurricular program. Providing adequate facilities, competent coaches, and integration with the physical education curriculum are strategic steps to maximize the benefits of swimming for students. Thus, extracurricular swimming programs can be one solution in improving the overall physical fitness and mental health of high school students.